Trademark in the Context of Competitive Environment – Between Regulations and Reality - Trendafilov, Dimitar (Economy and Business Yearbook, 2022)
A combination of principles influencing trademark law can lead to paradoxical situations of conflicts of interest and conflicting interpretations of the regulations. This article provides a brief overview of real market cases from the Common European Market, illustrating as cleanly as possible the tension between the right to property and the right to choose within a fair competitive environment. Two key phenomena shaping the meaning of the existence of the TM are covered also - similarity and dilution, the risk of which, and at the same time openness to interpretation, lead to discussions and to more questions than answers.